HUBUNGAN ANTARA KEPEMIMPINAN KEPALA SEKOLAH DENGAN HASIL KINERJA GURU SD NEGERI DI KECAMATAN PERCUT SEI TUAN - Demmu Karo-karo; Nelly Susanti (PGSD Universitas Negeri Medan, 2018)
This study aims to determine the relationship between the leadership of school principals and the results of the performance of public elementary school teachers in Percut Sei Tuan District. The research method used is a survey method with a type of quantitative research. To obtain the required data using a data collection tool in the form of documentation and questionnaires. Research in the Elementary School of Percut Sei Tuan as many as 66 schools. The number of samples is 6 schools based on the purposive sampling technique of 10% while the sample objects are 46 teachers. Based on data analysis, obtained an overview of the principal's leadership in the medium category at 48% and the teacher's performance in the medium category by 55%. The results of the correlation analysis between the leadership of the principal with the results of the teacher's performance obtained a value of rcount = 0,733 with rtable = 0,291 at the level of confidence of 95%. Thus the calculated value is greater than the rtable value, so the correlation is very significant. Test the hypothesis with the t test obtained tcount = 7.148 with ttable 1.680 at the confidence level of 95%.Keywords: Leadership, Principal, Teacher Performance Results